Series with Binomial-like Coefficients for the Investigation of Fractal Structures Associated with the Riemann Zeta Function - Igoris Belovas; Martynas Sabaliauskas; Lukas Kuzma (Fractal and Fractional, 2022)
The paper continues the study of efficient algorithms for the computation of zeta functions over the complex plane. We aim to apply the modifications of algorithms to the investigation of underlying fractal structures associated with the Riemann zeta function. We discuss the computational complexity and numerical aspects of the implemented algorithms based on series with binomial-like coefficients.